Mooc Method of Military Theory Course Based on Network Technology. Issue 4 (October 2020) - Zhao, Jing-Yuan
Abstract: With the development of information technology and the increasingly mature of network teaching, it has become an indispensable part of teaching reform to introduce moocs into the public curriculum system of colleges and universities. Combined with the characteristics of the Internet and big data, moocs and teaching have greatly improved the teaching effect and brought many advantages to the traditional teaching methods. Under the background of information technology era, military theory courses in colleges and universities have ushered in new development opportunities. Faced with the new teaching form of moocs, many colleges and universities have successively introduced military theory moocs, but the effect is not satisfactory. Therefore, it is very important to accelerate the combination of theory and online and optimize the teaching methods of military theory. The purpose of this paper is to explore the research on the application of military theory courses under the theoretical basis of network technology, so as to update the existing teaching Internet model by combining the application technology of Internet of things. This paper will adopt the research method of concrete analysis of specific problems and make data comparison to draw conclusions. The research results of this paper show that the advantages and disadvantages of moocs reflect the teaching reform path of military theory course based on moocs, which requires the establishment of professional moocs team and the provision of abundant course resources.